Spectroscopic Characterization of a VO²⁺ Complex of Oxodiacetic Acid and its Bioactivity on Osteoblast-like Cells in Culture - Rivadeneira, Josefina (2007)
The oxovanadium(IV) complex of oxodiacetic acid (H₂oda) of stoichiometry [VO(oda)(H₂O)₂], which presents an unprecedented tridentate OOO coordination, was thoroughly characterized by infrared, Raman, electronic, and electron paramagnetic resonance spectroscopies. The biological activity of the complex on the cell proliferation and differentiation was tested on osteoblast-like cells (MC3T3E1 osteoblastic mouse calvaria-derived cells and UMR106 rat osteosarcoma-derived cells) in culture. The complex caused inhibition of cellular proliferation in both osteoblast-like cells in culture, but the cytotoxicity was stronger in the normal (MC3T3E1) than in the tumoral (UMR106) osteoblasts. The effect of the complex in cell differentiation was tested through the specific activity of alkaline phosphatase of the UMR106 cells because they expressed a high activity of this enzyme. What occurs with other vanadium compounds [VO(oda)(H₂O)₂] is an inhibitory agent of osteoblast differentiation.